Materials for energy - Zhang, Sam (Boca Raton, FL : CRC Press, 2021)
Materials for Energy offers a comprehensive overview of the latest developments in materials for efficient and sustainable energy applications, including energy conversion, storage, and smart applications. Discusses a wide range of material types, such as nanomaterials, carbonaceous electrocatalysts and electrolytes, thin films, phase change materials, 2D energy materials, triboelectric materials, and membrane materials Describes applications that include flexible energy storage devices, sensors, energy storage batteries, fuel and solar cells, photocatalytic wastewater treatment, and more Highlights current developments in energy conversion, storage, and applications from a materials angle Aimed at researchers, engineers, and technologists working to solve alternative energy issues, this work illustrates the state of the art and latest technologies in this important field.
3.2.2.1 The Working Principle of Dielectric-to-Conductor Device -- 3.2.2.2 The Advantages of Dielectric-to-Conductor Device -- 3.2.2.3 Development of Dielectric-to-Conductor Paired Materials for TENGs -- 3.2.3 Semiconductor Device Structure -- 3.2.3.1 The Role of Semiconductor for TENGs -- 3.2.3.2 Semiconductor-to-Dielectric Device -- 3.2.3.3 Semiconductor-to-Conductor Device -- 3.3 The Output Enhancement Mechanism in TENGs -- 3.3.1 Selection of Paired Materials -- 3.3.2 Enhancement in Effective Contact -- 3.3.3 Modification of Material Composition -- 3.3.4 Control of Environmental Conditions
OCLC-licensed vendor bibliographic record.
Keywords: Electric batteries -- Materials; Energy storage -- Materials; Materials science; Sustainable engineering; Renewable energy sources -- Materials; SCIENCE / Energy; TECHNOLOGY / Material Science